Micro-milling of 65 vol% SiCp/Al composites with a novel laser-assisted hybrid process. Issue 16 (November 2020) - Zhao, Guolong; Mao, Pengcheng; Li, Liang; Iqbal, Asif; He, Ning
Abstract: Micro-machining of high-volume fraction SiC particles reinforced aluminum matrix (SiCp /Al) composites is characterized by high specific cutting forces, rapid tool wear, and deteriorated surface integrity. This study presents an innovative approach of laser-induced oxidation assisted micro-milling (LOMM) to improve micro-machinability of 65 vol% SiCp /Al composites. An easy-to-remove metamorphic layer, which is composed of an oxide layer and a sub-layer, is produced when the material is treated by a nanosecond laser in an oxygen-rich environment. The oxidation mechanism of the SiCp /Al composites is investigated. Under the average laser power of 8 W, scanning speed of 1 mm/s, track displacement of 10 μm and an oxygen-rich environment, the thicknesses of the oxide layer and sub-layer are 187.3 μm and 32.5 μm, respectively. The microstructure reveals that the oxide layer is porous, which causes generation of an extremely low cutting force of 0.3 N during its removal, thus, improving the machinability. Cavities and pits are distributed on the sub-layer. The material removal mechanisms in micro-milling of SiCp /Al composites include brittle fracture of the SiC reinforcements and ductile removal of the aluminum matrix. Small cavities and fissures are formed on the machined surface. The performance of the LOMM in respect of cutting forces and machined surface quality is compared with that of conventional micro-milling. The normal and thrust forces observed in LOMM are much lower than those in conventional micro-milling. The machined surface roughness ( Sa ) in LOMM is 147 nm, which is far superior than 471 nm of that in conventional micro-milling. The comparative study validates the practicability and high effectiveness of the proposed hybrid process.